The Transformative Leadership Strategy: Efforts to Improve The Positive Image of School - Halim, Abd; Rofiki, Moh. (Universitas Pahlawan Tuanku Tambusai, 2022)
Today's society thinks more realistically and critically in choosing educational institutions for their families. Therefore, educational institutions, through the principal as a manager, must carry out their duties with a transformative leadership style so that the positive image of the school increases so that it becomes the community's first choice to send their families to the school. This study presents a transformative leadership strategy for improving the school's image so that it exists amid competition between educational institutions. This research uses a qualitative case study approach. Methods of data collection using observation, interviews, and documentation. The object of this research is Islamic Senior High School of Nurul Jadid. The results showed that: Transformative leadership can create and enhance a positive image of the school where the positive image of Islamic Senior High School of Nurul Jadid can be seen from the achievements in academic and non-academic fields; The strategy used by the principal in improving the positive image of Islamic Senior High School of Nurul Jadid is by empowering and increasing the discipline of all school members which in its implementation is influenced by supporting factors, namely academic achievement, pleasing personality, and high socialization while the inhibiting factor is the lack of awareness of new teachers in educating students.